2022
DOI: 10.1016/j.abd.2021.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ocular psoriasis with meibography

Abstract: Background Previous studies has shown that dry eye test abnormalities, meibomian gland dysfunction (MGD), may occur in psoriasis. Objectives The authors aimed to evaluate the dry eye disease (DED), MGD, in psoriasis patients with meibography which is a current, objective, noninvasive method for patients with meibomian gland diseases, to investigate the relationship between disease severity and ocular involvement. Methods This study included 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…Previous studies have shown that DED is more prevalent among adults with psoriasis than among healthy controls; however, the present study is the first to establish a protective correlation between psoriasis severity, indicated by the PASI score, and DED [ 21 23 ]. Contrary to previous findings, the present study’s findings revealed that severe psoriasis protects against DED [ 21 , 24 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that DED is more prevalent among adults with psoriasis than among healthy controls; however, the present study is the first to establish a protective correlation between psoriasis severity, indicated by the PASI score, and DED [ 21 23 ]. Contrary to previous findings, the present study’s findings revealed that severe psoriasis protects against DED [ 21 , 24 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In a recent meta-analysis [ 15 ], the prevalence of MGD and DED in the general population were 21.2% and 8.1%, respectively, with some variation across studies [ 25 27 ]. In previous studies on adults with psoriasis, the rates of MGD and DED varied from 28–46% to 16–27%, respectively [ 21 24 ]. Consistent with the literature, the present study showed that the most commonly reported symptoms, such as burning, itching, tearing, and foreign body sensation, were associated with ocular surface diseases.…”
Section: Discussionmentioning
confidence: 99%
“…7 Kemeriz et al demonstrated that TBUT was lower, OSDI and corneal staining scores were higher, MGD was common, meibomian gland loss increased in psoriasis patients when compared to the control group, and there was no significant difference in the Schirmer test. 18 Taheri et al determined that TBUT and Schirmer test were lower in psoriasis patients, and a significant degree of meibomian gland atrophy was observed in meibography; however, there was no significant difference in the SM tube test (Echo Electricity, Japan), another test employed to analyze aqueous secretion. 19 Aragona et al demonstrated that the OSDI score, TBUT, Schirmer test, lipid layer thickness, corneal and conjunctival staining, squamous metaplasia in impression cytology, corneal esthesiometry findings, and MGD score were significantly worse in psoriasis patients, and there was no significant difference in the meibomian gland secretion in meibography.…”
Section: Discussionmentioning
confidence: 99%
“…21 Automatic meibography of lower eyelid glands enabled the imaging of Meibomian glands, assessment of their loss and hence-loss of lipid component of the precorneal tear film that prevents tear evaporation. 22 NIBUT indicates the stability of the tear film. 21 Decreased NIBUT suggests DES.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that subjects with lower lipid layer thicknesses have a higher probability of Meibomian gland dysfunction 21 . Automatic meibography of lower eyelid glands enabled the imaging of Meibomian glands, assessment of their loss and hence—loss of lipid component of the precorneal tear film that prevents tear evaporation 22 . NIBUT indicates the stability of the tear film 21 .…”
Section: Discussionmentioning
confidence: 99%